Biodiversity of Escherichia coli bacterial resistance to multidrug isolated on the Dumai coast of Indonesia: Biodiversity of Escherichia coli (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Feliatra F, Mardalisa M, Efendi I, Adelina A, Feliatra VA. 2021. Biodiversity of Escherichia coli bacterial resistance to multidrug isolated on the Dumai coast of Indonesia. Biodiversitas 23: 10-16. Anthropogenic pollution around the Dumai coast of Indonesia disturbs marine microorganisms, including commensal bacteria such as fecal Escherichia coli. Escherichia coli have often been used as a sensitive indicator for the spread of Antibiotic Resistance Genes (ARGs) among pathogens. This study aimed to analyze the development of E. coli resistance, originating from the Dumai sea waters using six antibiotics against seven E. coli isolates (E1, E4, E6, E8, E11, E13, and E15) at the five stations. Furthermore, a sensitivity test was performed on Mueller Hinton Agar (MHA) solid media, based on the Kirby-Bauer disk diffusion method. The results showed 100% E. coli isolates resistant to narrow-spectrum antibiotics (Penicillin, Isoniazid, Streptomycin, and Erythromycin) at the five stations. Meanwhile, high resistance of E. coli against the broad-spectrum antibiotics was observed in station 4 (mangrove habitat) existed in Chloramphenicol, whilst no resistance was found in Ciprofloxacin. Escherichia coli isolates showed Multidrug Resistant (MDR) index value higher than 0.2 which suggests there is a high-risk of antibiotics pollution in Dumai seawater. Bioinformatics analysis of 16S rRNA gene sequences represents the identity of E. coli isolates at the species level (97.84% - 99.74%). This study revealed the presence of antibiotic pollution in Dumai seawater which may impact public health. Hence, the local community must be discipline about the use of antibiotics freely.
Keywords: Antibiotic pollution, biodiversity, coastal water, Escherichia coli, multidrug resistant